Interaction of Transfusion Gelatin Molecule with Cetylpyridinium Chloride - Singh, R.P.; Arora, P.; Arora, S.K.; Chaudhary, R. (Asian Journal of Chemistry, 2010)
The experiments on the binding of cetyl pyridinium chloride to transfusion gelatin have been carried out at various pH, whereby the ionic type of binding has been studied by pHtitrations. The binding of this surfactant to protein molecule has also been studied with the help of viscometric method. The binding results have been explained in terms of binding and consequent structural disorganization within the protein molecule. The quantitative precipitation experiments suggested that the maximum precipitation and the complete dissolution of the precipitate took place at a definite ratio of the detergent concentration. The maximum amount of cationic detergent combined at each pH-value are approximately, corresponding to the base combining power of protein and so it is concluded that the first polar combination between protein molecule and cationic surfactant is accomplished at the point of the maximum precipitation. The pH-titration and dialysis equilibrium results pointed the involvement of anionic protein groups in interaction with the detergent cations. The logrithm of association constants (log K) were found to be 2.42 and 3.38 whereas the binding sites (n) 42 and 35 at pH 4.00 and 7.50, respectively. The lesser number of linkage sites showed the maximum number of moles of surfactant molecules combined upto statistical binding. The binding was found to be highly cooperative at higher concentrations of the surfactant. The flow behaviour indicated some conformational changes in the protein molecule. The pH-metric data strongly supported a mechanism in which binding between cationic surfactant and protein consists of an ionic binding while dialysis equilibrium corresponds to ionic as well as other types of binding. The precipitation and redissolution of surfactant-protein complex has been attributed to electrostatic linking above isoelectric point and nonelectrostatic type below this point involving forces which usually binds surfactant ions into micelles. It may be concluded that cationic surfactant-protein combination involved ionic hydrophobic and hydrogen bonding in forming complexes depending upon the pH and concentration of the cationic surfactant.